2020
DOI: 10.1002/chem.202002702
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optimization of Zeolitic Imidazolate Frameworks for the Oxygen Evolution Reaction

Abstract: Metal–organic frameworks/zeolitic imidazolate frameworks (MOFs/ZIFs) and their post‐synthesis modified nanostructures, such as oxides, hydroxides, and carbons have generated significant interest for electrocatalytic reactions. In this work, a high and durable oxygen evolution reaction (OER) performance directly from bimetallic Zn100−xCox‐ZIF samples is reported, without carrying out high‐temperature calcination and/or carbonization. ZIFs can be reproducibly and readily synthesized in large scale at ambient con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…[26][27][28][29][30][31][32] For example, Li et al reported that the CoZn bimetallic MOFs could exhibit OER activity with the overpotential of 320 mV at a current density of 10 mA cm −2 due to dimensionality and pore-geometry. [33] Furthermore, Bu et al reported that the CoNi bimetallic 2D-MOFs exhibited excellent OER activity with the overpotential of 240 mV at 10 mA cm −2 , thanks to the CoNi coupling effect and the unsaturated active sites. [34] However, although plenty of efficient Co MOFs-based bimetallic OER catalysts have been developed, to the best of our knowledge, the effect of different second metal on the OER catalytic performance of Co-based MOFs has not been systematically investigated.…”
mentioning
confidence: 99%
“…[26][27][28][29][30][31][32] For example, Li et al reported that the CoZn bimetallic MOFs could exhibit OER activity with the overpotential of 320 mV at a current density of 10 mA cm −2 due to dimensionality and pore-geometry. [33] Furthermore, Bu et al reported that the CoNi bimetallic 2D-MOFs exhibited excellent OER activity with the overpotential of 240 mV at 10 mA cm −2 , thanks to the CoNi coupling effect and the unsaturated active sites. [34] However, although plenty of efficient Co MOFs-based bimetallic OER catalysts have been developed, to the best of our knowledge, the effect of different second metal on the OER catalytic performance of Co-based MOFs has not been systematically investigated.…”
mentioning
confidence: 99%
“…In some synthesis process of electrocatalysts, like annealing, MOFs are usually used as precursors to obtained alloys, [14] doped oxides, [12a] heterojunctions, [15] metal‐nitrogen‐carbon system [9a,16] and other carbon based catalyst [17] . In some previous studies, the catalyst containing zinc element showed potential catalytic performance toward OER [18] . Meanwhile, the corresponding OER activity is also demonstrated for zinc‐air battery application [13] …”
Section: Methodsmentioning
confidence: 99%
“…The enhanced OER electrocatalytic performance is ascribed to the enlarged exposed active surface area, benefiting from the downsizing of MOF. [37] Similarly, Li et al recently used β-cyclodextrin (β-CD) as the modifier to regulate the size of MIL-53(Fe). The size of the synthesized MOFs can be well controlled by the introduction of different amounts of β-CD.…”
Section: Nanominiaturizationmentioning
confidence: 99%